2013
DOI: 10.1186/1476-4598-12-63
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of protumorigenic pathways by Insulin like growth factor binding protein2 and its association along with β-catenin in breast cancer lymph node metastasis

Abstract: BackgroundInsulin like growth factor binding proteins modulate the mitogenic and pro survival effects of IGF. Elevated expression of IGFBP2 is associated with progression of tumors that include prostate, ovarian, glioma among others. Though implicated in the progression of breast cancer, the molecular mechanisms involved in IGFBP2 actions are not well defined. This study investigates the molecular targets and biological pathways targeted by IGFBP2 in breast cancer.MethodsTranscriptome analysis of breast tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 48 publications
(54 reference statements)
1
16
0
Order By: Relevance
“…IGFBP2 is highly up regulated in GBM and its expression has been shown to be associated with increased cellular migration and invasion of several cancers [3][4][5][6][7][8][9]. Increased levels of IGFBP2 in GBM tissue and patient serum are potential diagnostic and prognostic markers [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…IGFBP2 is highly up regulated in GBM and its expression has been shown to be associated with increased cellular migration and invasion of several cancers [3][4][5][6][7][8][9]. Increased levels of IGFBP2 in GBM tissue and patient serum are potential diagnostic and prognostic markers [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…An IHC study on resected BC tissues showed a gradual elevation in IGFBP-2 expression from atypical hyperplasia through to carcinoma in situ and invasive carcinoma [35] and a TMA analysis of more than 4,000 primary invasive breast tumours indicated that an adverse survival outcome is correlated with IGFBP-2 expression in ERα negative tumours [41]. IGFBP-2 expression combined with cell adhesion protein, β-catenin, is linked with lymph node metastasis in BCs [42] and high levels of IGFBP-2 expression together with loss of PTEN expression are also associated with triple negative (TN) BC and poor survival rates [43]. IGFBP-2 is up-regulated in an in vitro model of Her-2+ BC [44] and recently multiple antigenic peptides (MAPs) comprising IGFBP-2 epitopes have been used to block tumour progression in a transgenic mouse model [37, 45].…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt signaling pathway is activated when the above homeostasis was broken resulting in an excess of β-catenin in hepatocytes. β-catenin also binds to transcription factors such as TCf/LEf to form a heterodimer and this regulates related target genes such as MMP-9, cyclin D1, c-myc and COX-2 (36)(37)(38). Thus, β-catenin regulates hepatocyte proliferation through the above process.…”
Section: Mirna Microarray Gene Microarray ---------------------------mentioning
confidence: 99%